Preparation method and application of zirconium and hydroxyapatite doped PVDF film
By using magnetron sputtering technology to deposit zirconium and hydroxyapatite on the surface of PVDF films, the shortcomings of existing PVDF films in bone integration, bone healing speed and antibacterial properties have been solved, and better biocompatibility and antibacterial properties have been achieved. Performance and osteogenic activity.
Patent Information
- Application Number
- CN202411502308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The existing PVDF films have shortcomings in poor bone integration, bone healing speed and effectiveness, and their antibacterial properties are poor.
Zirconium and hydroxyapatite are deposited on the surface of PVDF films through magnetron sputtering technology to form zirconium and hydroxyapatite-doped PVDF films, improving its biocompatibility, antibacterial properties and osteogenic activity.
The modified PVDF film significantly improves the adhesion, antibacterial activity and osteogenic ability to bone tissue, and enhances its application effect in bone tissue engineering.
Smart Images

Figure CN119455096A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material modification, and in particular relates to a preparation method and application of a zirconium and hydroxyapatite doped PVDF film. Background Art
[0002] PVDF (polyvinylidene fluoride polymer) piezoelectric film is a polyvinylidene fluoride piezoelectric film. The film has a piezoelectric effect, that is, when subjected to external force, polarized charges similar to the piezoelectric properties of natural bone tissue will appear on its surface. Since its introduction in 1969, PVDF piezoelectric film has been widely used in sensors and transducers in the fields of hydroacoustics, electroacoustics, medical devices, ion radiation, biomedicine, mechanics, optics and ultrasound. PVDF film not only exhibits excellent piezoelectric properties, but also has a large specific surface area, which enables it to effectively simulate the collagen fiber structure in the natural extracellular matrix. This film can instantaneously generate surface charges when undergoing small mechanical deformations, thereby enhancing its biocompatibility and functionality. Studies have shown that nanotopography and electrical signals in the extracellular microenvironment are crucial for bone regeneration, and nanostructures can regulate cell behavior through mechanical transmission, thereby inducing bone marrow mesenchymal stem cells (bMSC) to differentiate into osteoblasts. These characteristics make PVDF film show a wide range of application potential in many fields such as bone tissue engineering, bone repair, biosensors and drug delivery, and become an important material for research and development. With the advancement of technology, its application scope and effect are expected to be further expanded, providing more effective technical means for bone repair and regeneration. Although PVDF films have shown great potential in various applications, especially in the biomedical field, they still face some significant challenges and problems in practical applications. These problems include poor stability of electrical signals, insufficient regulation of bone regeneration, and slow bone healing. Some studies have applied zirconium oxide on this basis, but the preparation time of zirconium oxide is long and the effect is not very stable. In order to solve these problems, researchers have gradually paid attention to zirconium and hydroxyapatite nanomaterials, because they have been proven to have good bioactivity and excellent bone binding ability, which can effectively promote bone repair and regeneration.
[0003] In this context, sputtering coating technology has attracted widespread attention as an advanced material preparation method. This technology uses ions to bombard the surface of the target material, so that the atoms in the target material are knocked out and deposited on the surface of the substrate to form a thin film. This process usually relies on gas discharge to produce gas ionization. Through the action of the electric field, positive ions bombard the cathode target at a high speed, knocking out atoms or molecules, causing them to fly to the surface of the substrate to be plated, and finally deposited into a film. This method can ensure the uniformity and quality of the thin film.
[0004] Specifically, using magnetron sputtering technology, the researchers were able to effectively deposit zirconium and hydroxyapatite on the surface of the PVDF film. This not only enhanced the biocompatibility of the film, but also improved its piezoelectric properties, thereby improving its application in bone tissue engineering. Therefore, the study of combining these nanomaterials with PVDF is expected to promote the development of bone regeneration and repair technology in the future and provide more effective solutions for related fields.
[0005] Therefore, it is of great significance to develop a PVDF membrane with good biocompatibility, antibacterial activity, stable existence in the body and the ability to regulate bone regeneration. Summary of the invention
[0006] The purpose of the present invention is to address the problems existing in the prior art and provide a method for preparing and applying a zirconium and hydroxyapatite doped PVDF film. The zirconium and hydroxyapatite doped PVDF film prepared by the preparation method has excellent biocompatibility, antibacterial properties and osteogenesis induction ability, expands its application scenarios in the oral cavity and other parts, and effectively solves the shortcomings of existing PVDF films in terms of poor bone integration, bone healing speed and effectiveness.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a method for preparing a zirconium and hydroxyapatite doped PVDF film, wherein the zirconium content on the surface of the PVDF film is 46.7wt% by sputtering elemental zirconium and hydroxyapatite on the surface of the PVDF film using a magnetron sputtering method.
[0009] Furthermore, a method for preparing a zirconium and hydroxyapatite doped PVDF film comprises the following steps:
[0010] Step S1: pre-treating the PVDF film;
[0011] Step S2: sputtering elemental zirconium and hydroxyapatite on the surface of the PVDF film obtained in step S1 by magnetron sputtering to obtain a zirconium and hydroxyapatite doped PVDF film.
[0012] Furthermore, in step S2, the magnetron sputtering method for sputtering elemental zirconium and hydroxyapatite specifically controls the sputtering distance between the PVDF film and the elemental zirconium and hydroxyapatite, the sputtering power, the sputtering time, the reaction gas, the reaction gas flow rate, the substrate temperature and the gas pressure.
[0013] Preferably, in step S2, the sputtering distance is 3-10 cm.
[0014] Preferably, in step S2, the sputtering power is 50 W.
[0015] Preferably, in step S2, the sputtering time is 20-40 min.
[0016] Preferably, in step S2, the reaction gas is high-purity argon.
[0017] Preferably, in step S2, the reaction gas flow rate is 10-70 sccm.
[0018] Preferably, in step S2, the substrate temperature is room temperature-300°C.
[0019] Preferably, in step S2, the air pressure is 0.5-5Pa.
[0020] Preferably, the area size of the PVDF film is (1-3) cm×(1-3) cm.
[0021] Preferably, the thickness of the PVDF film is 28 μm.
[0022] Preferably, in step S1, the pretreatment method is to clean the PVDF film, dry it and store it in a vacuum.
[0023] Preferably, the cleaning method is ultrasonic cleaning with anhydrous ethanol for 15 min.
[0024] Preferably, the drying method is drying with nitrogen.
[0025] Furthermore, in step S2, the PVDF film is adhered to the conductive glue of the glass slide.
[0026] The second aspect of the present invention provides a zirconium and hydroxyapatite doped PVDF film prepared by the above preparation method.
[0027] The third aspect of the present invention provides an application of a zirconium and hydroxyapatite doped PVDF film prepared by the above preparation method, which is used in preparing materials for bone defect repair or tissue engineering.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] 1. The existing PVDF film surface nanostructure cannot establish good adhesion with bone tissue. The present invention effectively modifies the surface of the PVDF film with elemental zirconium and hydroxyapatite through magnetron sputtering technology, wherein the zirconium content is 46.7wt%, the fluorine content is 1.3wt%, and the P content is 0.5wt%, thereby improving the adhesion with bone tissue.
[0031] 2. The existing PVDF film has poor antibacterial performance. The zirconium and hydroxyapatite doped PVDF film prepared by the present invention can effectively stimulate macrophages to express T lymphocyte activation antigen (CD86), interleukin 1β (IL-1β), interferon regulatory factor 3 (IRF3), TNF receptor associated factor 6 (TRAF6) and nuclear factor receptor-κB (NF-κB), thereby exerting excellent antibacterial activity.
[0032] 3. The existing PVDF film has poor effects in bone bonding and bone repair. The zirconium and hydroxyapatite doped PVDF film prepared in the present invention can promote osteoblasts to express RUNX family transcription factor 2 (RUNX2), and it has good osteoinduction activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the method of modifying zirconium and hydroxyapatite doped PVDF film using magnetron sputtering technology in the present invention;
[0034] Figure 2 The overall imaging of the zirconium and hydroxyapatite doped PVDF film in Example 1 was performed using a scanning electron microscope at a magnification of 10,000 times;
[0035] Figure 3 The energy spectrum is generated by scanning the surface elements of the zirconium and hydroxyapatite doped PVDF films in Example 1 using the energy spectrum scanning module;
[0036] Figure 4 The relative expression of CD86 mRNA after culturing macrophages RAW264.7 with the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1 respectively;
[0037] Figure 5 The relative mRNA expression of IL-1β after culturing macrophages RAW264.7 using the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1 respectively;
[0038] Figure 6 The relative expression of IRF3 mRNA after culturing macrophages RAW264.7 using the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1 respectively;
[0039] Figure 7 is the relative expression of TRAF6 mRNA after culturing macrophages RAW264.7 using the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1;
[0040] Figure 8 is the relative expression of NF-κB mRNA after culturing macrophages RAW264.7 using the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1;
[0041] Fig. 9 is the relative expression of NF-κB mRNA after culturing macrophages RAW264.7 on the zirconium and hydroxyapatite doped PVDF film in Example 1, the hydroxyapatite doped PVDF film in Comparative Example 2, and the zirconium doped PVDF film in Comparative Example 3;
[0042] Fig.10 is the relative expression of MYD88 mRNA after culturing macrophages RAW264.7 on the zirconium and hydroxyapatite doped PVDF film in Example 1, the hydroxyapatite doped PVDF film in Comparative Example 2, and the zirconium doped PVDF film in Comparative Example 3;
[0043] Fig.11 is the relative expression of TRAF6 mRNA after culturing macrophages RAW264.7 on the zirconium and hydroxyapatite doped PVDF film in Example 1, the hydroxyapatite doped PVDF film in Comparative Example 2, and the zirconium doped PVDF film in Comparative Example 3;
[0044] Fig.12 is the relative expression of RUNX2 mRNA after culturing osteoblasts MT-3T3 on the zirconium and hydroxyapatite doped PVDF film in Example 1 and the PVDF film in Comparative Example 1;
[0045] Fig.13 It is the relative expression amount of IL-6 mRNA after culturing macrophages RAW264.7 on the zirconium and hydroxyapatite doped PVDF film in Example 1, the hydroxyapatite doped PVDF film in Comparative Example 2, and the zirconium doped PVDF film in Comparative Example 3. DETAILED DESCRIPTION
[0046] The following will be used in conjunction with examples to explain the implementation of the present invention in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The present invention provides a preparation method and application of a zirconium and hydroxyapatite doped PVDF film. The zirconium and hydroxyapatite doped PVDF film prepared by magnetron sputtering technology has better anti-inflammatory properties and osteogenic ability, and has a wider application prospect in clinical practice, and is suitable for: (1) providing a scaffold with better biocompatibility for bone defect repair in tissue engineering; (2) providing better antibacterial properties at the implant site and maintaining better osteogenic activity at the bone injury site.
[0048] The method for preparing the zirconium and hydroxyapatite doped PVDF film of the present invention comprises the following steps:
[0049] Step S1: pre-treating the PVDF film;
[0050] Step S2: sputtering elemental zirconium and hydroxyapatite on the surface of the PVDF film obtained in step S1 by magnetron sputtering to obtain a zirconium and hydroxyapatite doped PVDF film.
[0051] Preferably, in step S2, the magnetron sputtering method for sputtering zirconium and hydroxyapatite specifically controls the sputtering distance between the PVDF film and the elemental zirconium and hydroxyapatite to be 3-10 cm, the sputtering power to be 50 W, the sputtering time to be 20-40 min, the substrate temperature to be room temperature-300 ° C, the reaction gas to be high-purity argon, the reaction gas flow rate to be 10-70 sccm, and the gas pressure to be 0.5-5 Pa.
[0052] PVDF film, namely polyvinylidene fluoride film, was purchased from PolyK Company.
[0053] The reagents and instruments used in the following specific embodiments, unless otherwise specified, can all be purchased through conventional channels. The reagents or reaction raw materials used, unless otherwise specified, all use the initial concentration of each raw material in the purchased goods.
[0054] Example 1
[0055] A method for preparing a zirconium and hydroxyapatite doped PVDF film comprises the following steps:
[0056] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 minutes, blow dry with nitrogen and store in a vacuum.
[0057] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film treated in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install elemental zirconium and hydroxyapatite crystals in the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 5 Pa, and deposit elemental zirconium and hydroxyapatite on the PVDF film in an argon atmosphere, wherein the sputtering distance is 10 cm, the sputtering power is 50 W, the sputtering time is 20 min, the substrate temperature is 300 ° C, and the argon gas flow rate is 50 sccm, and finally a zirconium and hydroxyapatite doped PVDF film is obtained.
[0058] The method of doping PVDF film with zirconium and hydroxyapatite in this embodiment is as follows Figure 1 shown.
[0059] Example 2
[0060] A method for preparing a zirconium and hydroxyapatite doped PVDF film comprises the following steps:
[0061] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 min, blow dry with nitrogen and store in a vacuum.
[0062] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film treated in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install elemental zirconium and hydroxyapatite crystals in the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 0.5 Pa, and deposit elemental zirconium and hydroxyapatite on the PVDF film in an argon atmosphere, wherein the sputtering distance is 10 cm, the sputtering power is 50 W, the sputtering time is 30 min, the substrate temperature is room temperature, and the argon gas flow rate is 50 sccm, and finally a zirconium and hydroxyapatite doped PVDF film is obtained.
[0063] Example 3
[0064] A method for preparing a zirconium and hydroxyapatite doped PVDF film comprises the following steps:
[0065] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 min, blow dry with nitrogen and store in a vacuum.
[0066] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film treated in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install elemental zirconium and hydroxyapatite crystals in the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 0.5 Pa. In the argon atmosphere, elemental zirconium and hydroxyapatite are deposited on the PVDF film, wherein the sputtering distance is 5 cm, the sputtering power is 50 W, the sputtering time is 20 min, the substrate temperature is 200 ° C, and the argon gas flow rate is 50 sccm, and finally a zirconium and hydroxyapatite doped PVDF film is obtained.
[0067] Comparative Example 1
[0068] The PVDF film processing in this comparative example is the same as the S1 process in Example 1, except that the PVDF film obtained in this comparative example 1 is not modified by magnetron sputtering technology.
[0069] Comparative Example 2
[0070] A method for preparing a hydroxyapatite-doped PVDF film comprises the following steps:
[0071] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 minutes, blow dry with nitrogen and store in a vacuum.
[0072] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film treated in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install hydroxyapatite crystals in the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 5 Pa, and deposit hydroxyapatite on the PVDF film in an argon atmosphere, wherein the sputtering distance is 10 cm, the sputtering power is 50 W, the sputtering time is 20 min, the substrate temperature is 300 ° C, and the argon gas flow rate is 50 sccm, and finally a hydroxyapatite-doped PVDF film is obtained.
[0073] Comparative Example 3
[0074] A method for preparing a zirconium-doped PVDF film comprises the following steps:
[0075] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 min, blow dry with nitrogen and store in a vacuum.
[0076] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film treated in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install elemental zirconium in the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 5 Pa, and deposit elemental zirconium on the PVDF film in an argon atmosphere, wherein the sputtering distance is 10 cm, the sputtering power is 50 W, the sputtering time is 20 min, the substrate temperature is 300 ° C, and the argon gas flow rate is 50 sccm, and finally a zirconium-doped PVDF film is obtained.
[0077] Comparative Example 4
[0078] A method for preparing a zirconium and hydroxyapatite doped PVDF film comprises the following steps:
[0079] Step S1: Cut the PVDF film into a film with an area of 2 cm×2 cm, clean the film with anhydrous ethanol by ultrasonic for 15 minutes, blow dry with nitrogen and store in a vacuum.
[0080] Step S2: Adhere conductive glue to the glass slide, adhere the PVDF film processed in S1 to the conductive glue, and put the glass slide upside down into the magnetron sputtering chamber. Install elemental zirconium in the DC target area of the magnetron sputtering, close the chamber, introduce high-purity argon gas, keep the gas pressure at 5 Pa, and deposit elemental zirconium on the PVDF film in the argon atmosphere.
[0081] Step S3: Install hydroxyapatite crystals on the DC target area of magnetron sputtering. After closing the chamber, introduce high-purity argon gas to keep the gas pressure at 5 Pa, and deposit hydroxyapatite on the PVDF film obtained in step S2 under the argon atmosphere.
[0082] The sputtering distance was 10 cm, the sputtering power was 50 W, the sputtering time was 20 min, the substrate temperature was 300 °C, and the argon gas flow rate was 50 sccm.
[0083] Finally, zirconium and hydroxyapatite doped PVDF film was obtained.
[0084] Test example
[0085] (1) Physical and chemical properties test
[0086] The zirconium and hydroxyapatite doped PVDF film prepared in Example 1 was imaged as a whole at a magnification of 10,000 times using a scanning electron microscope. Figure 2 As shown, the surface of the PVDF film modified by zirconium and hydroxyapatite is smoother.
[0087] The zirconium and hydroxyapatite doped PVDF films prepared in Example 1 were scanned for surface elements using the energy spectrum scanning module. The results are as follows: Figure 3As shown in Table 1, zirconium and hydroxyapatite with stable contents were generated, wherein the zirconium content was 46.7wt%, the fluorine content was 1.3wt%, and the P content was 0.5wt%.
[0088] Table 1 Specific component results of energy spectrum scanning
[0089]
[0090] (2) Antibacterial activity detection
[0091] The PVDF films prepared in Example 1 and Comparative Example 1 were respectively soaked in alcohol and then fully sterilized by ultraviolet irradiation.
[0092] They were placed in a six-well cell culture plate and inoculated with 50% macrophage RAW264.7 cells. Two days later, when the density increased to 80%, the cells were collected for qPCR experiments to detect the expression of T lymphocyte activation antigen (CD86), interleukin 1β (IL-1β), interferon regulatory factor 3 (IRF3), TNF receptor-associated factor 6 (TRAF6) and nuclear factor receptor-κB (NF-κB). Statistical analysis and drawing were performed using ImageJ software.
[0093] The results are as follows Figure 4-8 As shown, the modified PVDF film in Example 1 can promote the expression of inflammatory factors such as CD86, IL-1β, IRF3, TRAF6 and NF-κB in macrophages, indicating that it enhances the anti-inflammatory activity of macrophages.
[0094] In this test example, the same method was used to compare the expression of TNF receptor-associated factor 6 (TRAF6), nuclear factor receptor-κB (NF-κB), and myeloid differentiation factor 88 (MYD88) in Example 1, Comparative Example 2, and Comparative Example 3. The results are as follows: Figure 9-11 As shown, the anti-inflammatory activity of the PVDF films in Comparative Examples 2 and 3 is relatively low.
[0095] (3) Osteogenic activity detection
[0096] The PVDF films prepared in Example 1 and Comparative Example 1 were respectively soaked in alcohol and then fully sterilized by ultraviolet irradiation.
[0097] They were placed in a six-well cell culture plate and inoculated with MT-3T3 osteoblasts at a density of 50%. Two days later, when the density increased to 80%, the cells were collected for qPCR experiments to detect the expression of RUNX family transcription factor 2 (RUNX2). ImageJ software was used for statistical analysis and drawing.
[0098] The results are as follows Fig.12As shown, the modified PVDF film in Example 1 can upregulate the expression of RUNX2 transcription factor in osteoblasts, indicating that it has excellent osteogenic activity.
[0099] In this test example, the same method was used to compare the expression of interleukin 6 (IL-6) in Example 1, Comparative Example 2 and Comparative Example 3. The results are as follows: Fig.13 As shown, the osteogenic activity of the PVDF films in Comparative Examples 2 and 3 is relatively low.
[0100] Although the embodiments of the present invention have been shown and described, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A method for preparing a zirconium and hydroxyapatite doped PVDF film, characterized in that: The zirconium content on the surface of the PVDF film was 46.7wt% by sputtering elemental zirconium and hydroxyapatite on the surface of the PVDF film using a magnetron sputtering method.
2. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 1, characterized in that: The following steps are involved: Step S1: pre-treating the PVDF film; Step S2: sputtering elemental zirconium and hydroxyapatite on the surface of the PVDF film obtained in step S1 by magnetron sputtering to obtain a zirconium and hydroxyapatite doped PVDF film.
3. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 1, characterized in that: In step S2, the magnetron sputtering method for sputtering elemental zirconium and hydroxyapatite specifically controls the sputtering distance between the PVDF film and the elemental zirconium and hydroxyapatite, the sputtering power, the sputtering time, the reaction gas, the reaction gas flow rate, the substrate temperature and the gas pressure.
4. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 3, characterized in that: The sputtering distance is 3-10 cm, the sputtering power is 50 W, and the sputtering time is 20-40 min.
5. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 3, characterized in that: The reaction gas is high-purity argon gas, the reaction gas flow rate is 10-70 sccm, the substrate temperature is room temperature-300° C., and the gas pressure is 0.5-5 Pa.
6. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 1, characterized in that: In the step S1, the pretreatment method is to clean the PVDF film, dry it and store it in a vacuum.
7. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 1, characterized in that: In the step S2, the PVDF film is adhered to the conductive glue on the glass slide.
8. The method for preparing a zirconium and hydroxyapatite doped PVDF film according to claim 1, characterized in that: In the step S1, the area of the PVDF film is (1-3) cm×(1-3) cm, and the thickness is 28 μm.
9. A zirconium and hydroxyapatite doped PVDF film prepared by the preparation method according to any one of claims 1 to 8.
10. Application of zirconium and hydroxyapatite doped PVDF film prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Used in preparing materials for bone defect repair or tissue engineering.